Effect of Curcumin Supplement on Pulmonary Functions, Total and Differential White Blood Cell Count, Serum Level of Leptin and Body Mass Index in a Sample of Iraqi Patients with Chronic Bronchial Asthma - Sura Abbas Khdair; Manal Khalid Abdulridha; Mostafa Abdal Fatah (College of Pharmacy / Mustansiriyah University, 2019)
Asthma is a heterogeneous disease, usually characterized by chronic airway inflammation together with increased oxidative stress that lead to clinical symptoms of asthma.    Obesity is a known risk factor of asthma as the obesity is correlated with systemic inflammation and airway restriction. Curcumin, a natural product derived from the rhizomes of Curcuma longa (Turmeric), has a wide range of beneficial properties including anti-inflammatory and weight reducing agent. This study was designed to evaluate the effect of curcumin as supplement therapy on the pulmonary function, total and differential white blood cell count and metabolic status of chronic bronchial asthmatic patients. It is a prospective randomized controlled interventional study carried out on 40 patients visiting Al-Yarmouk teaching hospital and conducted from October 2017 to April 2018. The patients were allocated into group1; include 17 asthmatic patients assigned to receive conventional therapy for asthma alone, and group 2; include 23 asthmatic patients assigned to receive conventional therapy for asthma plus 750 mg curcumin capsule twice daily for two months. Results revealed significant improvement in forced expiratory volume in one second (FEV1) and the ratio of forced expiratory volume in one second to forced vital capacity (FEV1/FVC) in group 2 patients after two months(P<0.01). The total white blood cell count didn't show any difference after treatment except decrease in neutrophil count after curcumin supplement (p< 0.05). The leptin level and body mass index present with no significant difference in both groups after two months (p >0.05).